Drought-induced embolism in current-year shoots of two Mediterranean evergreen oaks - Pinto, Clara A. (2015)
threatened by the increasing water deficits related to climate change. To contribute to the understanding of the capacity of these oaks to withstand severe drought we assessed the vulnerability to xylem embolism and the anatomical traits in current-year shoots. Data were collected in mature trees at two sites, in central/ coastal and southern/inland Portugal. In situ safety margins to hydraulic failure were evaluated from long-term predawn and midday leaf water potential records. Results showed that xylem vulnerability to embolism was similar in Q. ilex and Q. suber. The 50% loss in hydraulic conductivity (Wxyl,50PLC) was observed at xylem water potentials of 2.9 and 3.2 MPa in shoots of Q. suber and Q. ilex, respectively. Values of mean vessel diameter of Q. suber shoots at both sites suggest an intra-species adaptation to the local water availability, with larger vessels at the more mesic site. In situ hydraulic safety margins observed in shoots showed that, even during the driest periods, both oaks lived comfortably above the most critical embolism thresholds. However, the hydraulic safety margins were narrower in the driest site. Results are relevant to the understanding of survival, growth, and functional behaviour of evergreen oaks in Mediterranean climates, under recurrent/seasonal drought conditions